Fabrication and characterization of carbon nanotube array electrodes with gold nanoparticle tips - Yun, YeoHeung; Dong, Zhongyun; Shanov, Vesselin N.; Doepke, Amos; Heineman, William R.; Halsall, H. Brian; Bhattacharya, Amit; Wong, Danny K.Y.; Schulz, Mark J. (Sensors and actuators. B, Chemical, 2008)
In this work we fabricated 8 mm long aligned multi-walled carbon nanotube array electrodes and electrochemically deposited gold nanoparticles in a controlled manner onto the nanotube tips at the top of the array. A soldering technique was also developed to provide reliable electrical contact between the carbon nanotubes at the bottom of the array and copper on a patterned printed circuit board. The top surfaces of the nanotube tower electrodes were activated using a reactive ion etcher prior to gold deposition. Electrodeposition of Au particles on the plasma-treated tower electrodes was performed over a range of deposition times and potentials. Cyclic voltammetry and electrochemical impedance spectroscopy analyses showed that the Au-deposited carbon nanotube array electrodes were successfully fabricated. The new electrodes will be the foundation for further biosensor development using self-assembled monolayers and bio-conjugation of antibodies for novel label-free immunosensing.